Evaluation of a Motion Correction Algorithm for C-Arm Computed Tomography Acquired During Transarterial Chemoembolization - Becker, Lena S.; Gutberlet, Marcel; Maschke, Sabine K.; Werncke, Thomas; Dewald, Cornelia L. A.; von Falck, Christian; Vogel, Arndt; Kloeckner, Roman; Meyer, Bernhard C.; Wacker, Frank; Hinrichs, Jan B. (Cardiovascular and interventional radiology, 2021)
Purpose The aim of this retrospective study was to evaluate the feasibility of a motion correction 3D reconstruction prototype technique for C-arm computed tomography (CACT). Material and Methods We included 65 consecutive CACTs acquired during transarterial chemoembolization of 54 patients (47 m,7f; 67 ± 11.3 years). All original raw datasets (CACT Org ) underwent reconstruction with and without volume punching of high-contrast objects using a 3D image reconstruction software to compensate for motion (CACT MC_bone ;CACT MC_no bone ). Subsequently, the effect on image quality (IQ) was evaluated using objective (image sharpness metric) and subjective criteria. Subjective criteria were defined by vessel geometry, overall IQ, delineation of tumor feeders, the presence of foreign material-induced artifacts and need for additional imaging, assessed by two independent readers on a 3-(vessel geometry and overall IQ) or 2-point scale, respectively. Friedman rank-sum test and post hoc analysis in form of pairwise Wilcoxon signed-rank test were computed and inter-observer agreement analyzed using kappa test. Results Objective IQ as defined by an image sharpness metric, increased from 273.5 ± 28 (CACT Org ) to 328.5 ± 55.1 (CACT MC_bone ) and 331 ± 57.8 (CACT MC_no bone ; all p < 0.0001). These results could largely be confirmed by the subjective analysis, which demonstrated predominantly good and moderate inter-observer agreement, with best agreement for CACT MC_no bone in all categories (e.g., vessel geometry : CACT Org : κ = 0.51, CACT MC_bone : κ = 0.42, CACT MC_no bone : κ = 0.69). Conclusion The application of a motion correction algorithm was feasible for all data sets and led to an increase in both objective and subjective IQ parameters. Level of Evidence 3